THE INFLUENCE OF THE SOCIAL ENVIRONMENT ON THE FORMATION OF PERSONALITY - Abduqahharova Nigora Adhamjon qizi,; Toshpulatov Ibrohim Ikromjonovich , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article describes in detail the factors influencing the formation of a person and his personality, the influence of the macro and micro environment surrounding a person, the stages of child development and the importance of upbringing, the unique ideas of Eastern thinkers and Uzbek intellectuals.